2018
DOI: 10.1021/jacs.8b04437
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Catalysts Are Superior: Suppressing Product Inhibition by Anchimeric Assistance in Four-Component Catalytic Machinery

Abstract: Three distinct four-component supramolecular nanorotors, prepared by varying the rotator's structure and keeping all other components constant, exhibit rotational frequencies that differ by almost 2 orders of magnitude. When the rotors were used as catalyst for two click reactions, the product yield correlated with the speed of the machine, e.g., 20% at 0.50 kHz, 44% at 20 kHz and 62% at 42 kHz. The kinetic effect on the product yield is attributed to the ability of the rotating catalysts to displace the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 28 publications
3
59
0
3
Order By: Relevance
“…Chemists are at the beginning of building synthetic catalysts with similar functions, with the long‐term aim to control chemical pathways in more complex chemical mixtures . In this context, there is increasing interest in synthetic catalysts that can be switched by external stimuli or cofactors . Most of these studies have been carried out using relatively simple hydrolysis reactions and organocatalytic reactions, and the number of transition‐metal catalysts that have a switching function is very limited .…”
Section: Figurementioning
confidence: 99%
“…Chemists are at the beginning of building synthetic catalysts with similar functions, with the long‐term aim to control chemical pathways in more complex chemical mixtures . In this context, there is increasing interest in synthetic catalysts that can be switched by external stimuli or cofactors . Most of these studies have been carried out using relatively simple hydrolysis reactions and organocatalytic reactions, and the number of transition‐metal catalysts that have a switching function is very limited .…”
Section: Figurementioning
confidence: 99%
“…In another interesting example, coordination chemistry was used to prepare supramolecular nano-rotors where both the stator and the rotor are porphyrin derivatives connected by 1,4-diazabicyclo[2.2.2]octane (DABCO) as an axle between two porphyrin moieties, and two copper I ions ( Fig. 3) [24][25][26][27][28][29][30][31]. Variable temperature NMR analysis showed that the rotational speeds at 25 °C vary roughly from 0.5 to 100 kHz, mainly controlled by the rotor structure, solvent system, presence of Cu I , and addition of a suitable chelating agent.…”
Section: Sandwich-type Complexesmentioning
confidence: 99%
“…Interestingly, when the rotors were used as a catalyst for click reactions, the product yields correlated with the speed of the machine. The dependence of yield on rotation speed is attributed to the ability of a rotating catalyst to displace the product more efficiently from the active site [30].…”
Section: Sandwich-type Complexesmentioning
confidence: 99%
“…In order to network stand-alone molecular [10][11][12] or supramolecular [13][14][15][16][17][18][19][20] devices, the functional entities need to be linked by fast chemical communication without harmful interference. All receptors and emitters involved in communication thus need to be highly dynamic and selective with regard to signal uptake, information processing and signal release (= output).…”
mentioning
confidence: 99%